Facile synthesis and thermal performances of stearic acid/titania core/shell nanocapsules by sol-gel method - Tahan Latibari S.; Mehrali M.; Mehrali M.; Afifi A.B.M.; Mahlia T.M.I.; Akhiani A.R.; Metselaar H.S.C. (Elsevier Ltd, 2023)
Chemical stability; Encapsulation; Heat storage; Nanocapsules; Sol-gel process; Sol-gels; Stearic acid; Thermal conductivity; Titanium; Titanium dioxide; Chemical interactions; Controlled synthesis; Encapsulation efficiency; Nano-encapsulation; Phase change property; Stability and reliabilities; Thermal Performance; Titanium tetraisopropoxide; Phase change materials; encapsulation; experimental study; fatty acid; gel; oxide; performance assessment; pH; stabilization; temperature effect; thermal conductivity; weight